Giant Solitary Cyst at the Site of Knee Osteoarthritis: Treatment with a Synthetic Resorbable Bone Graft Substitute and Primary Total Knee Arthroplasty - Andreas Thiery; Octavian Tapos; Konstantinos Anagnostakos (Case Reports in Orthopedics)
A 48-year-old male patient presented in our department with knee osteoarthritis and a giant cystic lesion of the lateral femoral condyle. Bone biopsy of the lesion was performed. Histopathological examination confirmed the presence of a solitary bone cyst. The patient was treated by curettage of the cyst, filling with a synthetic resorbable bone graft substitute (Cerament™), and primary, cruciate-retaining total knee arthroplasty. 4 months after surgery, complete osseointegration of the bone graft substitute was evident on X-rays. The use of modern bone graft substitutes might be a novel alternative to other established techniques in the management of large bone lesions, even at the site of primary total knee replacement.